Opinion 2409: Pomachilius variegatus Schwarz, 1904 (Insecta, Coleoptera, Elateridae): conservation of the specific name by suppression of the name Aeolus variegatus Curtis, 1839 not approved - ICZN (Bulletin of Zoological Nomenclature, 2018)
The International Commission on Zoological Nomenclature has declined to use its plenary power to conserve the specific name Pomachilus variegatus Schwarz, 1904 by suppressing the senior secondary homonym Aeolus variegatus Curtis, 1839.
Keywords: Nomenclature; taxonomy; Coleoptera; ELATERIDAE; Aeolus variegatus; Pomachilius variegatus; Pomachilius subfasciatus; click beetle; Neotropical